Auxin Homeostasis in Arabidopsis Ovules Is Anther-Dependent at Maturation and Changes Dynamically upon Fertilization - Larsson, Emma; Vivian-Smith, Adam; Offringa, Remko; Sundberg, Eva (Frontiers in Plant Science, 2017)
The plant hormone auxin is a vital component for plant reproduction as it regulates the development of both male and female reproductive organs, including ovules and gynoecia. Furthermore, auxin plays important roles in the development and growth of seeds and fruits. Auxin responses can be detected in ovules shortly after fertilization, and it has been suggested that this accumulation is a prerequisite for the developmental reprogramming of the ovules to seeds, and of the gynoecium to a fruit. However, the roles of auxin at the final stages of ovule development, and the sources of auxin leading to the observed responses in ovules after fertilization have remained elusive. Here we have characterized the auxin readout in Arabidopsis ovules, at the pre-anthesis, anthesis and in the immediate post-fertilization stages, using the R2D2 auxin sensor. In addition we have mapped the expression of auxin biosynthesis and conjugation genes, as well as that of auxin transporting proteins, during the same developmental stages. These analyses reveal specific spatiotemporal patterns of the different auxin homeostasis regulators. Auxin biosynthesis genes and auxin transport proteins define a pre-patterning of vascular cell identity in the pre-anthesis funiculus. Furthermore, our data suggests that auxin efflux from the ovule is restricted in an anther-dependent manner, presumably to synchronize reproductive organ development and thereby optimizing the chances of successful fertilization. Finally, de novo auxin biosynthesis together with reduced auxin conjugation and transport result in an enhanced auxin readout throughout the sporophytic tissues of the ovules soon after fertilization. Together, our results suggest a sophisticated set of regulatory cascades that allow successful fertilization and the subsequent transition of the female reproductive structures into seeds and fruits.